Edge effects at multifunctional agro-landscapes in Jember, Indonesia, on the augmentation of butterfly diversity - AGUNG SIH KURNIANTO; NANANG TRI HARYADI; NILASARI DEWI; MIFTACHURROHMI MIFTACHURROHMI; ANDI ROHMANA; GITINDRA IKHLASUL AMAL; LUHUR SEPTIADI; ANGGUN SAUSAN FIRDAUS; NUR LAILA MAGVIRA (Society for Indonesian Biodiversity, 2023)
Abstract. Kurnianto AS, Haryadi NT, Dewi N, Miftachurrohmi, Rohmana A, Amal GI, Septiadi L, Firdaus AS, Magvira NL. 2023. Edge effects at multifunctional agro-landscapes in Jember, Indonesia, on the augmentation of butterfly diversity. Biodiversitas 24: 2231-2241. Butterflies are important pollinators and bioindicator communities in agro-landscapes. Assessing changes in butterfly communities, such as abundance and diversity, is essential in evaluating the response of butterflies to ecosystem disturbance. However, edge effects on agro-landscapes are highly influenced by land management. This study aims to objectively investigate the interactions between agroforestry management, including mono-shade, complex, and agroforestry-monoculture systems, with butterfly diversity to assess the impact of edge effects on butterfly communities. Sampling was conducted using Van Sommeren traps (T=150 cm; D=30 cm) baited with fermented bananas. Each trap was hung three meters high on a tree with three replicates in one location. Within 24 hours, the butterflies were collected, dried in an oven for 3x24 hours, and identified. The ecological indices were calculated using PAST 3.26, including the Shannon-Wiener index, the Simpson dominance index (D), the Simpson diversity index (1_D), the Margalef index, and the Evenness index. Therefore, 61 specimens, including 59 Nymphalidae and 2 Pieridae, were successfully collected. There are Nympahlidae families: Amathusia phidippus Linnaeus, 1763 (1), Elymnias casiphone Hübner, 1824 (2), Elymnias hypermnestra Linnaeus, 1763 (2), Euthalia aconthea Cramer, 1779 (1), Euthalia monina Fabricius, 1787 (1), Junonia atlites Linnaeus, 1763 (1), Junonia iphita Cramer, 1782 (1), Lethe europa Fabricius, 1775 (1), Melanitis leda Linnaeus, 1758 (24), Melanitis phedima Cramer, 1782 (4), Mycalesis fuscum Felder, 1860 (2), Mycalesis horsfieldi Moore, 1892 (1), Mycalesis janardana Moore, 1857 (6), Mycalesis nala Felder, 1859 (1), Mycaleses perseus Fabricius, 1775 (1), Mycalesis sudra Felder, 1867 (2), Orsotriaena cinerea Butler, 1867 (1), Orsotriaena medus Fabricius, 1775 (2), Polyura athamas Drury, 1773 (3), Polyura schreiberi Godart, 1824 (1), Tanaecia trigerta Moore, 1857 (1). There are families Pieridae: Leptosia nina Fabricius, 1793 (1), Eurema blanda Boisduval, 1836 (2). Comparison between complex and monoculture sites showed substantial differences. Meanwhile, there was no significant difference between mono-shade and monoculture sites. Butterfly diversity at the three locations was categorized as moderate. The highest diversity was observed in mono-shade sites. The three similarity indices showed that the agroforestry complex and monoculture locations have high similarity. Melanitis leda Linnaeus, 1758 was found in 3 sites and commonly found in complex sites (16), followed by monoculture (6) and mono-shade (2). This study indicated that edge effects have a significant influence, especially on the diversity of butterflies in the monoculture area.